2020
DOI: 10.1016/j.imr.2020.100407
|View full text |Cite
|
Sign up to set email alerts
|

Herbal medicine and pattern identification for treating COVID-19: a rapid review of guidelines

Abstract: a b s t r a c tBackground:: Coronavirus disease 2019 is pandemic and has caused illness to many people worldwide. This review aimed to summarize and analyze the herbal formulae provided by the guidelines for their pattern identifications (PIs) and compositions of herbs to treat patients with COVID-19. Methods:: We searched 7 data sources for eligible traditional medicine guidelines up to March 6, 2020 and found a total of 28 traditional medicine guidelines that provide treatment measures for COVID-19. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
192
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 209 publications
(207 citation statements)
references
References 9 publications
1
192
0
3
Order By: Relevance
“…This enzyme is vital for the replication of SARS-CoV and thus could be suggested as a potential treatment agent against SARS-CoV-2 and supportive care agent for patients with COVID-19 [22]. The guidelines and the herbal formulas used for the supportive care of patients with COVID-19 were revised by Ang et al [23]. However, the potential preventive effect of these formulas should be confirmed with rigorous and prospective clinical studies [21].…”
Section: The Role Of Bioactive Ingredients In Supporting the Human Immentioning
confidence: 99%
“…This enzyme is vital for the replication of SARS-CoV and thus could be suggested as a potential treatment agent against SARS-CoV-2 and supportive care agent for patients with COVID-19 [22]. The guidelines and the herbal formulas used for the supportive care of patients with COVID-19 were revised by Ang et al [23]. However, the potential preventive effect of these formulas should be confirmed with rigorous and prospective clinical studies [21].…”
Section: The Role Of Bioactive Ingredients In Supporting the Human Immentioning
confidence: 99%
“…Historically, traditional herbal medicines have been used in the past to control and to treat epidemic outbreaks [155] including the past epidemic outbreaks, such as SARS and H1N1 influenza [156,157]. To date, China and South Korea have issued traditional medicinal treatment guidelines on the prevention and treatment of COVID-19 [158]. It is reported that greater than 85% of SARS-CoV-2-infected patients in China had received some forms of Traditional Chinese Medicine (TCM) treatments [159].…”
Section: Traditional Herbal Medicinesmentioning
confidence: 99%
“…In particular, the frequently used herbs in the recommended herbal formulae for the treatment of pediatric COVID-19 lack diversity compared to the adults [22]. In the recommendations on adult treatment for COVID-19, the herb Glycyrrhizae Radix et Rhizoma was the herb with the highest frequency of usage [22]. This might be due to the difference in the spectrum of diseases between the children and the adults.…”
Section: Discussionmentioning
confidence: 99%